Pemberdayaan Masyarakat Desa Pandak Melalui Budaya Baksos sebagai Budaya Lokal Masyarakat Indonesia - Muh Aswar; Arzaq Maulana Faisal; Riska Adinanra; Nur Rahma Akmal; Sumitra Sardan; Rosita Rosita; Dewi Magefira; Rahma Syam; Nurul Hikmah; Muh Fathur Rahman R; Ainul Fahmi (LP2M Universitas Muhammadiyah Enrekang, 2021)
Social Service is one of the cultures that exist in Indonesian society and has been passed down from generation to generation, from generation to generation. Nowadays, social service has begun to be forgotten and eroded by technological developments. The culture of social service is a culture that must be maintained and revived in every community. The culture of social service can provide several benefits to social life, because through social service activities, friendship and community cooperation can be improved. In addition to the community, social services can also provide benefits to the environment, because with regular social services the environment will be maintained and with a well-maintained environment it will create a healthy environment for the community.